Bahasa Inggris - Adrian Suharsono; Siti Rahayu; Fitri Novika Widjaja (Universitas Muhammadiyah Pontianak, 2026)
This study examines how e-service quality, food quality, and brand image influence customer loyalty, with perceived value and customer satisfaction as mediators in Indonesia’s online food delivery industry. Using a quantitative causal approach with data from 226 active users and PLS-SEM analysis, the results show that e-service quality significantly improves loyalty, while brand image increases customer satisfaction. Food quality does not significantly affect loyalty, and both mediators are insignificant. The findings indicate that digital service performance and brand image are more crucial for customer satisfaction and loyalty than food quality.